Diabetic Neuropathy - Zakin, Elina; Abrams, Rory; Simpson, David M. (Seminars in Neurology, 2019)
Diabetes mellitus is becoming increasingly common worldwide. As this occurs, there will be an increase in the prevalence of known comorbidities from this disorder of glucose metabolism. One of the most disabling adverse comorbidities is diabetic neuropathy. The most common neuropathic manifestation is distal symmetric polyneuropathy, which can lead to sensory disturbances, including diminished protective sense, making patients prone to foot injuries. However, focal, multifocal, and autonomic neuropathies are also common. Diabetic nerve pain and Charcot osteoarthropathy are advanced neuropathic conditions that portend a severe deterioration in quality of life. To combat these symptoms, along with glycemic control and establishment of health care systems to educate and support patients with the complexities of diabetes, there are pharmacologic remedies to ameliorate the neurologic symptoms. Several guidelines and review boards generally recommend the use of tricyclic antidepressants, serotonin/norepinephrine-reuptake inhibitors, α-2-delta ligands, and anticonvulsants as medications to improve painful diabetic neuropathy and quality of life.
Keywords: diabetic neuropathy; distal symmetric polyneuropathy; neuropathic pain